2012
DOI: 10.2147/ijn.s26935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin nanoliposomes on C6 glioma cells through induction of type III programmed cell death

Abstract: Background:Quercetin has been shown to induce apoptosis in a number of cancer cell lines, but a quercetin-loaded nanoliposomal formulation with enhanced antitumor activity in C6 glioma cells and its effect on cancer cell death has not been well studied. The aim of this study was to examine if quercetin-loaded liposomes (QUE-NL) has enhanced cytotoxic effects and if such effects involve type III programmed cell death in C6 glioma cells. Methods: C6 glioma cells were treated with QUE-NL and assayed for cell surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…We then examined the phosphorylation of JAK2, which has been reported to correlate with cell death induction, using western blotting. 12 The dynamic activation of JAK2 was observed 12–24 h after QUE-NL treatment. We therefore presumed that JAK2 was involved in QUE-NL-induced C6 glioma cell death.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We then examined the phosphorylation of JAK2, which has been reported to correlate with cell death induction, using western blotting. 12 The dynamic activation of JAK2 was observed 12–24 h after QUE-NL treatment. We therefore presumed that JAK2 was involved in QUE-NL-induced C6 glioma cell death.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, treatment with QUE-NLs resulted in necrotic cell death, because it did not trigger the activation of caspases from the mitochondrial pathway. 12 QUE-NL-induced necrotic cell death was partially reversible by pretreatment with AG490, a JAK2 (Janus kinase 2) specific inhibitor. 13 Paradoxically, AG490 effectively enhanced the effects of QUE-NL-induced apoptosis.…”
mentioning
confidence: 98%
“…Oral administration of 30 mg/kg of free and nano-quercetin three times per week at week 3, 4, 5 post tumor inoculation to A549 lung tumor xenograft mice decreased the tumor size 20% and 40%, respectively, but they did not change animal body weight [105]. Wang G et al demonstrated that quercetin nanoliposomes decreased the viability of C6 glioma cells, and induced necrotic death of those cells [118]. Dhawan S et al found that the intravenous administration of quercetin improved memory retention and increased brain antioxidant capacity in rats with aluminium-induced dementia, and quercetin encapsulated SLNs significantly improved those beneficial effects by more than two-fold [119].…”
Section: Improvement Of Characteristics and Bioactivities Of Phytomentioning
confidence: 99%
“…Quercetin is an important factor for plant secondary metabolism; it has a wide range of biological activity and is also a promising candidate for prevention and treatment of various cancers (Joanna et al, 2011;Wang et al, 2012). The quercetin glycosides and free quercetin in buckwheat flowers, leaves, stems, and achenes were discovered by Dadakova in 2010.…”
Section: Introductionmentioning
confidence: 99%